LINC00518 Promotes Cell Proliferation by Regulating the Cell Cycle of Lung Adenocarcinoma Through miR-185-3p Targeting MECP2 - Han, Xu; Wu, Jixiang; Zhang, Yajun; Song, Jianxiang; Shi, Zhan; Chang, Huiwen (Frontiers in Oncology, 2021)
Previous studies have shown that long non-coding RNA (lncRNA) and long intergenic non-protein coding RNA 00518 (LINC00518) are essential for the cell growth and metastasis of human cancer. However, the role of LINC00518 in non-small cell lung cancer (NSCLC) is still unknown. This research puts emphasis on the function of LINC00518 on the cell growth of NSCLC. The lncRNA and RNA expression were measured by using qRT-PCR. Protein levels were measured using western blotting analysis. CCK-8, colony formation assays and transwell assay were performed to evaluate the cell proliferation ability and invasion. Bioinformatic analysis and luciferase reporter assays were carried to confirm the mechanism of LINC00518 in NSCLC. We found that LINC00518 was highly expressed in NSCLC specimens and the high-expression was negatively correlated with the overall survival rates. This finding was also proved in the NSCLC cell line. Through a series of in vitro experiments, we proved that LICN00518 promotes the invasion and migration of NSCLC by regulating the cell cycle. LICN00518 up-regulates the expression of MECP2 by mutagenesis of miR-185-3p. This result suggests that LICN00518 can be used as a survival indicator and potential therapeutic target for NSCLC patients.